Preparation process of metalized polymer flame-retardant fiber material and application of metalized polymer flame-retardant fiber material in wearable health monitoring equipment

Through the preparation process of metallic polymer flame retardant fiber materials, the problem of insufficient flame retardant performance and insufficient performance excellent performance in the high -end medical field of traditional fiber materials, and realized the preparation of high -performance composite materials. It is suitable for high temperature and high -end medical care application.

CN119352297APending Publication Date: 2025-01-24HEYE HEALTH TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411631991.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional fiber materials have problems such as insufficient flame retardant performance and insufficient performance excellence in the high-end medical field, which limits their use in cutting-edge medical application scenarios.

Method used

The preparation process of a metallic polymer flame retardant fiber material, including the cleaning, pre -treatment, dopamine modification, chemical metallicization of aramid fiber, and a combination of composite lotion with polyacrylate to form high -performance composite materials.

Benefits of technology

By improving the surface bonding strength between the fiber and the resin matrix, the overall performance of the composite material is improved, and the flame retardant performance, tensile strength, weaving and breathability of the material are enhanced, making it suitable for high temperature and high-end medical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352297A_ABST
    Figure CN119352297A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation process of a metalized polymer flame-retardant fiber material and application of the metalized polymer flame-retardant fiber material in wearable health monitoring equipment. The preparation method comprises the following steps: aramid fiber surface cleaning, aramid fiber pretreatment, aramid fiber modification with dopamine, aramid fiber surface chemical plating metallization, aramid fiber bundle composite material preparation, polyacrylate composite emulsion preparation, and metallization of a polymer flame-retardant fiber material. According to the invention, an oil removal and coarsening integrated method, a chemical reduction surface metallization method and a chemical plating metallization treatment method are creatively combined, and the prepared material has excellent tensile force, air permeability and flame retardance; the wearable health monitoring equipment using the obtained material has the advantages of accuracy and comfort in monitoring physiological indexes and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation process of a metallized polymer flame-retardant fiber material and application in wearable health monitoring equipment, belonging to the technical field of new materials. Background Art

[0002] Metal polymer flame retardant fiber material is a new type of material that combines the properties of metal and polymer flame retardant properties. With the advancement of science and technology, this type of material has shown broad application prospects in the field of medical and health care, but the application of traditional fiber materials faces some challenges and problems: on the one hand, the flame retardant properties of traditional fibers are poor, and it is difficult to meet the strict requirements of high-end medical fields for material fire safety; on the other hand, traditional fibers lack excellent properties such as tension and weavability, which limits their use in cutting-edge medical application scenarios.

[0003] Aramid fiber is a new type of polymer fiber. Its full name is aromatic polyamide fiber. The main chain of the molecule is composed of benzene rings and amide bonds. Aramid fiber has excellent tensile strength, weaving properties, conductivity, air permeability and temperature resistance. Aramid fiber also has a long life cycle. Compared with common traditional composite fiber reinforcement materials such as glass fiber and carbon fiber, aramid fiber is low in cost but its mechanical properties are not as good as aramid fiber; carbon fiber has high strength but the cost is too high. Aramid fiber combines the strengths of these two fibers, with the characteristics of tensile strength, weaving properties, high temperature resistance, etc. It is an ideal composite material reinforcement. Therefore, compared with other fibers, it is conducive to the preparation of metallized polymer flame retardant fiber materials. Summary of the invention

[0004] In view of the above problems, the present invention provides a preparation process of a metallized polymer flame-retardant fiber material.

[0005] The present invention provides a preparation process of a metallized polymer flame-retardant fiber material, comprising the following steps: step (1) cleaning the surface of aramid fiber, step (2) pre-treating the aramid fiber, step (3) modifying the aramid fiber by dopamine, step (4) chemically metallizing the surface of the aramid fiber, step (5) preparing an aramid fiber tow composite material, step (6) preparing a polyacrylate composite emulsion, and step (7) preparing the metallized polymer flame-retardant fiber material; Wherein, step (2) aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a potassium hydroxide solution, and continuously stirred with ultrasonic vibration, and roughened, and then cleaned with distilled water; the degreased and roughened aramid fiber is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in the sensitizing solution and stir it continuously to make a layer of easily oxidized substances adsorbed on the fiber surface. During the activation treatment, the activation solution is reduced to form catalytic crystal nuclei, which are adsorbed on the surface of the fiber and then rinsed with distilled water; Activation: Place the sensitized fiber in the activation solution and stir it vigorously to form a layer of palladium metal particles with catalytic activity on the fiber surface, and then rinse it with distilled water; Reduction: The activated fiber is placed in a sodium hypophosphite solution for reduction treatment to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber Dopamine hydrochloride and distilled water are used to prepare a dopamine solution, and tris(hydroxymethyl)aminomethane is added to adjust the pH value; then the aramid fiber bundle pretreated in step (2) is wound on a rack and placed in the dopamine solution for stirring, and then the fiber is washed with water and dried for later use.

[0006] Preferably, step (1) cleaning the surface of the aramid fiber Place the fiber bundle in a conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner for cleaning, wash the fiber after ultrasonic cleaning with acetone with clean water, put it in an oven for drying, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a potassium hydroxide solution and continuously stirred with ultrasonic vibration to roughen it, and then cleaned with distilled water. The degreased and roughened aramid fiber is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in a sensitizing solution (a mixture of stannous chloride and hydrochloric acid) and stir it continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface. During the activation treatment, the activation solution is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface. Then rinse it with distilled water to prevent the catalytic crystal nuclei from being washed away. Activation: Place the sensitized fiber in an activation solution (a mixture of palladium chloride and hydrochloric acid) and stir vigorously to form a layer of palladium metal particles with catalytic activity on the fiber surface, and then rinse it with distilled water; Reduction: The activated fiber is placed in a sodium hypophosphite solution for reduction treatment to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber A dopamine solution is prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane is added to adjust the pH value, and the solution is placed in a magnetic stirrer; then the aramid fiber tow pretreated in step (2) is wound on a rack and placed in the dopamine solution, the magnetic stirrer is turned on and stirred separately, and then the fiber is washed with water and dried for later use; Step (4): Chemical metallization of aramid fiber surface Prepare the main salt (copper sulfate), complexing agent (sodium citrate), reducing agent (sodium hypophosphite), stabilizer (sodium thiosulfate), compounding agent (sodium potassium tartrate), etc.; dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the pre-dissolved main salt solution; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution and filter the plating solution; Step (5) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin, add DDS (epoxy resin and DDS (diaminodiphenyl sulfone) mixture) curing agent, and stir until the solution is light yellow and transparent; put it into a vacuum oven for degassing; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold, put it into the oven, heat it and increase the temperature to cure the resin; Step (6) Preparation of polyacrylate composite emulsion Add deionized water to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel and preheat it in a water bath; add the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the dispersed nano flame retardant powder solution to the four-necked flask and heat it in a water bath at the same time, stir the powder and the core pre-emulsion liquid evenly by high-speed stirring, add the initiator (NH4)2S2O8 and the buffer Na2HPO4, and stir mechanically at high speed to form a core layer emulsion; After the core layer emulsion is formed, an emulsifier (nonylphenol polyoxyethylene ether ammonium sulfate, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture) is added and the shell pre-emulsion is added dropwise at a uniform speed through a constant pressure funnel; after the shell pre-emulsion is added dropwise, an initiator (NH4)2S2O8 and a buffer Na2HPO4 are added and then kept warm; after the reaction is completed, the material is discharged, cooled to room temperature and then the polyacrylate composite emulsion is allowed to stand; Step (7) Metallized polymer flame retardant fiber material The aramid fiber bundle composite material prepared in step (5) is spread flat on a clean glass plate, and the polyacrylate composite emulsion prepared in step (6) is dipped into a paint brush and evenly coated on the surface. The two are placed together in a vacuum drying oven to dry, and the glass plate is taken out and the aramid fiber bundle composite material is peeled off from the glass plate.

[0007] Preferably, step (1) cleaning the surface of the aramid fiber Take a 3-4 m long fiber bundle and place it in a 300-400 mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it 3-4 times at 30-4 kHz, each time for 20-30 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for later use.

[0008] The advantage of adopting the present invention is that, through its cleaning technology, the cleaning liquid can more fully infiltrate the aramid fiber, thereby improving the surface bonding strength between the fiber and the resin matrix and enhancing the overall performance of the composite material; the cleaning process can remove impurities and oil stains on the fiber surface, making the fiber surface cleaner and smoother, which helps to increase the service life of the fiber.

[0009] Preferably, step (2) aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a 30-35 g / L potassium hydroxide solution at 40-45°C and continuously stirred with ultrasonic vibration, and roughened, and then cleaned with distilled water, and the degreased and roughened aramid fiber is placed in a dilute slightly acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in a sensitizing solution (10~15g·L -1 of stannous chloride and 30~35ml·L -1 Hydrochloric acid (d = 118 ~ 119g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: Place the sensitized fiber in an activation solution (0.4~0.5g·L -1 of palladium chloride and 10ml·L -1 Hydrochloric acid (d = 118 ~ 119 g cm -3 ) in a mixed solution) with strong stirring to form a layer of catalytically active palladium metal particles on the fiber surface, which was then rinsed with distilled water; Reduction: Place the activated fiber in a 25~30g·L -1Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface.

[0010] The invention has the advantages that the aramid fiber is subjected to the steps of degreasing, roughening, sensitization, activation and reduction, and the use of a sensitizing solution and an activating solution prepared from palladium chloride and stannous chloride respectively is beneficial to improving the interfacial bonding performance between the fiber and a matrix material: ultrasonic oscillation stirring is used to improve the interfacial bonding performance between the fiber and a matrix material such as a resin, thereby changing the surface roughness of the fiber, reducing the entanglement between the fibers, facilitating the preparation of the aramid fiber bundle composite material, and improving the air permeability of the material.

[0011] Preferably, in step (3), dopamine-modified aramid fiber A 2-3 g / L dopamine solution is prepared using dopamine hydrochloride and distilled water, and tris(hydroxymethyl)aminomethane is added to adjust the pH value to 8.5-8.6. The solution is placed in a magnetic stirrer. The aramid fiber tow pretreated in step (2) is then wound on a rack and placed in the dopamine solution. The magnetic stirrer is turned on and stirred at 30°C. The fiber is then washed with water and dried for later use.

[0012] The advantage of adopting the present invention is that dopamine-modified aramid fiber is conducive to improving the adhesion of dopamine, so that dopamine can be deposited on the surface of the aramid fiber. At the same time, the treated fiber material is stirred in a magnetic stirrer to increase the surface activity of the fiber, which is conducive to the subsequent chemical metallization of the aramid fiber surface and improves the tensile properties of the fiber.

[0013] Preferably, step (4) chemically metallizes the aramid fiber surface. Weigh 15-25 g of main salt (copper sulfate), 50-80 g of complexing agent (sodium citrate), 70-90 g of reducing agent (sodium hypophosphite), 0.40-0.50 mg of stabilizer (sodium thiosulfate), and 0.04-0.05 mg of compounding agent (sodium potassium tartrate); dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the pre-dissolved main salt solution; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution and filter the plating solution.

[0014] The invention has the advantages that the chemical metallization process on the surface of the aramid fiber is conducive to the chemical reaction of the plating solution in the fiber material, and at the same time, sodium thiosulfate and sodium hypophosphite are conducive to the stability and reduction of the chemical metallization process, thereby improving the area coverage of the chemical metallization and improving the conductivity of the aramid fiber; at the same time, the chemical metallization can retain the tensile properties of the material for the aramid fiber.

[0015] Preferably, step (5) preparing the aramid fiber tow composite material Heat and stir E-51 epoxy resin at 125-130°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:30-100:32), stir until the solution is light yellow and transparent; put it into a vacuum oven at 75-80°C for degassing for 25-30 minutes; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 120-130°C for 1.5-2 hours, then heat it to 200-210°C and heat it for 1.5-2 hours to cure the resin.

[0016] The invention has the advantages that the E-51 epoxy resin has excellent adhesion to the aramid fiber composite material, and the E-51 epoxy resin solution added with the DDS curing agent can form good resin curing with the aramid fiber, thereby ensuring the integrity and stability of the composite material; the epoxy resin has good thermal stability, and the degassed resin can still maintain good performance in a high temperature environment, which is beneficial to the curing of the composite material resin under high temperature oven conditions.

[0017] Preferably, step (6) preparation of polyacrylate composite emulsion Add deionized water to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and preheat it in a water bath to 60-65°C; add the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder into the four-necked flask according to the test formula, and heat it in a water bath at 77-78°C. After the powder and the core pre-emulsion liquid are evenly mixed by high-speed stirring, add the initiator (NH4)2S2O8 (2-3mL / h) and the buffer Na2HPO4 (2-3mL / h), and form a core layer emulsion after high-speed mechanical stirring for 1.5-2h; After the core layer emulsion is formed, an emulsifier (ammonium sulfate of nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether, a mixture of sodium dodecyl sulfate and water; the water-oil ratio is 1:60~1:65) is added and the shell pre-emulsion is uniformly added through a constant pressure funnel (2~2.5h / 5min); after two hours, the shell pre-emulsion is added, the temperature of the water bath is raised to 75~80℃, and the initiator (NH4)2S2O8 (2~3mL / h) and the buffer Na2HPO4 (2~3mL / h) are added and kept warm for 1 hour; after the reaction is completed, the material is discharged at 74~76℃, cooled to room temperature and then the polyacrylate composite emulsion is allowed to stand.

[0018] The invention has the advantages that, in the preparation of the polyacrylate composite emulsion, the surface of the nano flame retardant powder is modified, a specific coating layer is introduced, the compatibility of the nano flame retardant powder with the polyacrylate emulsion is improved, and the stability and flame retardant performance of the composite emulsion are improved; at the same time, the nano flame retardant powder is evenly dispersed in the polyacrylate emulsion through high-speed stirring to avoid agglomeration, thereby improving the dispersion effect and stability of the nano flame retardant powder in the polyacrylate emulsion and enhancing the flame retardant performance and comprehensive performance of the composite emulsion.

[0019] Preferably, step (7) metallizes the polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (5) on a clean glass plate, dip the polyacrylate composite emulsion prepared in step (6) with a paint brush, evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 90-95°C for 9-10 minutes, take out the glass plate, and peel off the aramid fiber bundle composite material from the glass plate.

[0020] The advantages of the present invention are that the flame retardant property of the aramid fiber bundle composite material can be enhanced by coating the aramid fiber bundle composite material with a flame retardant, and the tensile strength and chemical stability of the material can be improved by coating the material with a polyacrylate composite emulsion and drying it in a vacuum drying oven; the fiber material treated by degreasing, roughening, sensitizing, activating and reducing steps and coating can resist the erosion of the material by high temperature and extend its service life.

[0021] In summary, the present invention has the following beneficial effects: 1. The advantage of the present invention is that, through its cleaning technology, the cleaning liquid can more fully infiltrate the aramid fiber, thereby improving the surface bonding strength between the fiber and the resin matrix and improving the overall performance of the composite material. The cleaning process can remove impurities and oil stains on the fiber surface, making the fiber surface cleaner and smoother, which helps to increase the service life of the fiber; 2. The present invention has the advantages that the aramid fiber is subjected to the steps of degreasing, roughening, sensitization, activation and reduction, and the use of a sensitizing solution and an activating solution prepared from palladium chloride and stannous chloride, respectively, is conducive to improving the interfacial bonding performance between the fiber and the matrix material: the interfacial bonding performance between the fiber and the matrix material such as the resin is improved by ultrasonic oscillation stirring, thereby changing the surface roughness of the fiber, reducing the entanglement between the fibers, and being conducive to the preparation of aramid fiber bundle composite materials, and improving the air permeability of the material; 3. The advantages of the present invention are that the dopamine-modified aramid fiber is conducive to improving the adhesion of dopamine, so that dopamine can be deposited on the surface of the aramid fiber. At the same time, the treated fiber material is stirred in a magnetic stirrer, which increases the surface activity of the fiber, is conducive to the subsequent chemical metallization of the aramid fiber surface, and improves the tensile properties of the fiber; 4. The present invention has the advantages that the chemical metallization process on the surface of aramid fiber is conducive to the chemical reaction of the plating solution in the fiber material, and sodium thiosulfate and sodium hypophosphite are conducive to the stability and reduction of the chemical metallization process, thereby increasing the area coverage of chemical metallization and improving the conductivity of aramid fiber; at the same time, chemical metallization can retain the tensile properties of the material for aramid fiber; 5. The advantages of the present invention are that the E-51 epoxy resin has excellent adhesion to the aramid fiber composite material, and the E-51 epoxy resin solution added with the DDS curing agent can form a good resin curing with the aramid fiber, ensuring the integrity and stability of the composite material; the epoxy resin has good thermal stability, and the degassed resin can still maintain good performance in a high temperature environment, which is conducive to the curing of the composite material resin under high temperature oven conditions; 6. The advantages of the present invention are that, in the preparation of the polyacrylate composite emulsion, the nano flame retardant powder is surface modified and a specific coating layer is introduced to improve its compatibility with the polyacrylate emulsion, thereby improving the stability and flame retardant performance of the composite emulsion; at the same time, the nano flame retardant powder is evenly dispersed in the polyacrylate emulsion through high-speed stirring to avoid agglomeration, thereby improving the dispersion effect and stability of the nano flame retardant powder in the polyacrylate emulsion, and enhancing the flame retardant performance and comprehensive performance of the composite emulsion; 7. The advantage of adopting the present invention is that coating the aramid fiber bundle composite material with a flame retardant can enhance the flame retardant properties of the material. The material is coated with a polyacrylate composite emulsion and dried in a vacuum drying oven, which can improve the tensile strength of the material and improve the chemical stability. The fiber material treated by degreasing, roughening, sensitizing, activating and reducing steps and coating can resist the erosion of the material by high temperature and extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart for preparing a metallized polymer flame-retardant fiber material. DETAILED DESCRIPTION

[0023] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0024] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.

[0025] Example 1

[0026] Step (1) Aramid fiber surface cleaning Take a 4m long fiber bundle and place it in a 400mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it three times at 40kHz, each time for 30 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a 35 g / L potassium hydroxide solution at 45°C and continuously stirred with ultrasonic vibration to roughen the fiber, and then cleaned with distilled water. The roughened aramid fiber is placed in a dilute acid and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in a sensitizing solution (15 g·L -1 of stannous chloride and 35ml·L -1 Hydrochloric acid (d = 119 g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: The sensitized fibers were placed in an activation solution (0.5 g L -1 of palladium chloride and 10ml·L -1 Hydrochloric acid (d = 119 g cm -3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: The activated fiber was placed in 30g·L -1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber A 2 g / L dopamine solution is prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane is added to adjust the pH value to 8.5, and the solution is placed in a magnetic stirrer; the aramid fiber tow pretreated in step (2) is then wound on a rack and placed in the dopamine solution, the magnetic stirrer is turned on, and stirred at 30° C.; the fiber is then washed with water and dried for later use; Step (4) Chemical metallization of aramid fiber surface Weigh 25g of main salt (copper sulfate), 80g of complexing agent (sodium citrate), 90g of reducing agent (sodium hypophosphite), 0.50mg of stabilizer (sodium thiosulfate), and 0.05mg of compounding agent (sodium potassium tartrate); dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the main salt solution dissolved in advance; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and vibrate with ultrasound; adjust the plating solution value with acid or alkali solution, and filter the plating solution; Step (5) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin at 130°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:32), and stir until the solution is light yellow and transparent; put it into a vacuum oven at 80°C for degassing for 30 minutes; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 130°C for 2 hours, then increase the temperature to 210°C and heat it for 2 hours to cure the resin; Step (6) Preparation of polyacrylate composite emulsion Deionized water was added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and the mixture was preheated to 65°C in a water bath. The core pre-emulsion (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder were added to the four-necked flask and heated in a water bath at 78°C. After the powder and the core pre-emulsion were evenly mixed by high-speed stirring, the initiator (NH4)2S2O8 (3mL / h) and the buffer Na2HPO4 (3mL / h) were added, and the core layer emulsion was formed after high-speed mechanical stirring for 1.5h. After the core layer emulsion is formed, an emulsifier (ammonium sulfate of nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture; water-to-oil ratio is 1:65) is added and the shell pre-emulsion is uniformly added dropwise through a constant pressure funnel (2.5h / 5min); after 2 hours, the addition of the shell pre-emulsion is completed, the water bath temperature is raised to 80°C, and the initiator (NH4)2S2O8 (3mL / h) and the buffer Na2HPO4 (3mL / h) are added and kept warm for 30h; after the reaction is completed, the material is discharged at 74°C, cooled to room temperature and allowed to stand. The polyacrylate composite emulsion is applied to the aramid fiber tow composite material prepared in step (5); Step (7) Metallized polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (5) on a clean glass plate, dip a paint brush into the polyacrylate composite emulsion prepared in step (6), evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 95°C for 10 minutes, take out the glass plate, and peel off the aramid fiber bundle composite material from the glass plate.

[0027] Example 2

[0028] Step (1) Aramid fiber surface cleaning Take a 3.8m long fiber bundle and place it in a 350mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it three times at 37kHz, each time for 29 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber prepared in step (1) is placed in a 34 g / L potassium hydroxide solution at 44°C and continuously stirred with ultrasonic vibration to remove oil stains on the fiber surface and roughen it, and then cleaned with distilled water; neutralization: the aramid fiber degreased and roughened through the degreasing, roughening, sensitization, activation and reduction steps is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: The neutralized aramid fiber was placed in a sensitizing solution (14 g·L -1 of stannous chloride and 34ml·L -1 Hydrochloric acid (d = 119 g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: The sensitized fiber was placed in an activation solution (0.48 g·L -1 of palladium chloride and 9.8 ml·L -1 Hydrochloric acid (d = 119 g cm -3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: The activated fiber was placed in 28g·L -1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber A 1.8 g / L dopamine solution is prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane is added to adjust the pH value to 8.48, and the solution is placed in a magnetic stirrer; the aramid fiber tow pretreated in step (2) is then wound on a rack and placed in the dopamine solution, the magnetic stirrer is turned on, and stirred at 28° C.; the fiber is then washed with water and dried for later use; Step (4): Chemical metallization of aramid fiber surface Weigh 23g of main salt (copper sulfate), 70g of complexing agent (sodium citrate), 75g of reducing agent (sodium hypophosphite), 0.48mg of stabilizer (sodium thiosulfate), and 0.05mg of compounding agent (sodium potassium tartrate); dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the pre-dissolved main salt solution; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution, and filter the plating solution; Step (5) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin at 129°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:31), and stir until the solution is light yellow and transparent; put it into a vacuum oven at 79°C for degassing for 29 minutes; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 128°C for 1.9 hours, then increase the temperature to 208°C and heat it for 1.9 hours to cure the resin; Step (6) Preparation of polyacrylate composite emulsion Deionized water was added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and the water bath was preheated to 64°C; according to the test formula, the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder were added to the four-necked flask and heated in a water bath at 78°C. After the powder and the core pre-emulsion liquid were mixed evenly by high-speed stirring, the initiator (NH4)2S2O8 (2.7mL / h) and the buffer Na2HPO4 (2.7mL / h) were added, and the core layer emulsion was formed after high-speed mechanical stirring for 1.9h; After the core layer emulsion is formed, an emulsifier (nonylphenol polyoxyethylene ether ammonium sulfate, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture; water-oil ratio is 1:64) is added and the shell pre-emulsion is uniformly added through a constant pressure funnel (2.4h / 5min); after two hours, the shell pre-emulsion is added, the water bath temperature is raised to 80°C, and the initiator (NH4)2S2O8 (2.7mL / h) and buffer Na2HPO4 (2.7mL / h) are added and kept warm for 0.9 hours; after the reaction is completed, the material is discharged at 75°C, cooled to room temperature and then allowed to stand to form a polyacrylate composite emulsion; Step (7) Metallized polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (5) on a clean glass plate, dip the polyacrylate composite emulsion prepared in step (6) with a paint brush, evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 94°C for 9.8 minutes, take out the glass plate, and peel off the aramid fiber bundle composite material from the glass plate.

[0029] Example 3

[0030] Step (1) Aramid fiber surface cleaning Take a 3.7m long fiber bundle and place it in a 350mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it three times at 36kHz, each time for 28 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber prepared in step (1) is placed in a 33 g / L potassium hydroxide solution at 43°C and continuously stirred with ultrasonic vibration to remove oil stains on the fiber surface and roughen it, and then washed with distilled water; neutralization: the aramid fiber degreased and roughened through the degreasing, roughening, sensitization, activation and reduction steps is placed in a dilute acid, and the alkali remaining on the fiber surface is washed with distilled water; Sensitization: The neutralized aramid fiber was placed in a sensitizing solution (12 g·L -1 of stannous chloride and 33ml·L -1 Hydrochloric acid (d = 118 g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: The sensitized fibers were placed in an activation solution (0.46 g·L -1 of palladium chloride and 9.6 ml·L -1 Hydrochloric acid (d = 119 g cm-3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: The activated fiber was placed in 27g·L -1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber A 1.7 g / L dopamine solution is prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane is added to adjust the pH value to 8.46, and the solution is placed in a magnetic stirrer; the aramid fiber tow pretreated in step (2) is then wound on a rack and placed in the dopamine solution, the magnetic stirrer is turned on, and stirred at 28° C.; the fiber is then washed with water and dried for later use; Step (4): Chemical metallization of aramid fiber surface Weigh 20g of main salt (copper sulfate), 60g of complexing agent (sodium citrate), 70g of reducing agent (sodium hypophosphite), 0.46mg of stabilizer (sodium thiosulfate), and 0.04mg of compounding agent (sodium potassium tartrate); dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the main salt solution dissolved in advance; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution, and filter the plating solution; Step (5) Preparation of aramid fiber tow composite material: Heat and stir E-51 epoxy resin at 128°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:32), and stir until the solution is light yellow and transparent; put it into a vacuum oven at 78°C for degassing for 28 minutes; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 126°C for 1.8 hours, then increase the temperature to 207°C and heat it for 1.8 hours to cure the resin; Step (6) Preparation of polyacrylate composite emulsion Deionized water was added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and the water bath was preheated to 63°C; according to the test formula, the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder were added to the four-necked flask and heated in a water bath at 77°C. After the powder and the core pre-emulsion liquid were mixed evenly by high-speed stirring, the initiator (NH4)2S2O8 (2.6mL / h) and the buffer Na2HPO4 (2.6mL / h) were added, and the core layer emulsion was formed after high-speed mechanical stirring for 1.8h; After the core layer emulsion is formed, an emulsifier (ammonium sulfate of nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture; water-oil ratio is 1:60) is added and the shell pre-emulsion is uniformly added through a constant pressure funnel (2.3h / 5min); after two hours, the shell pre-emulsion is added, the water bath temperature is raised to 80°C, the initiator (NH4)2S2O8 (2.6mL / h) and the buffer Na2HPO4 (2.6mL / h) are added and kept warm for 0.8 hours; after the reaction is completed, the material is discharged at 74°C, cooled to room temperature and then the polyacrylate composite emulsion is allowed to stand; Step (7) Metallized polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (5) on a clean glass plate, dip the polyacrylate composite emulsion prepared in step (6) with a paint brush, evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 93°C for 9.7 minutes, take out the glass plate, and peel off the aramid fiber bundle composite material from the glass plate.

[0031] Example 4

[0032] Step (1) Aramid fiber surface cleaning Take a 3.6m long fiber bundle and place it in a 350mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it three times at 35kHz, each time for 27 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber prepared in step (1) is placed in a 32 g / L potassium hydroxide solution at 40°C and continuously stirred with ultrasonic vibration to remove oil stains on the fiber surface and roughen it, and then washed with distilled water; neutralization: the aramid fiber degreased and roughened through the degreasing, roughening, sensitization, activation and reduction steps is placed in a dilute acid, and the alkali remaining on the fiber surface is washed with distilled water; Sensitization: The neutralized aramid fiber was placed in a sensitizing solution (11 g·L -1 of stannous chloride and 30ml·L -1 Hydrochloric acid (d = 118 g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: The sensitized fibers were placed in an activation solution (0.44 g L -1 of palladium chloride and 9.5 ml·L -1Hydrochloric acid (d = 119 g cm -3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: The activated fiber was placed in 25g·L -1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber A 1.5 g / L dopamine solution is prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane is added to adjust the pH value to 8.46, and the solution is placed in a magnetic stirrer; the aramid fiber tow pretreated in step (2) is then wound on a rack and placed in the dopamine solution, the magnetic stirrer is turned on, and stirred at 27° C.; the fiber is then washed with water and dried for later use; Step (4): Chemical metallization of aramid fiber surface Weigh 18g of main salt (copper sulfate), 55g of complexing agent (sodium citrate), 75g of reducing agent (sodium hypophosphite), 0.45mg of stabilizer (sodium thiosulfate), and 0.03mg of compounding agent (sodium potassium tartrate); dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the pre-dissolved main salt solution; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution, and filter the plating solution; Step (5) Preparation of aramid fiber tow composite material: Heat and stir E-51 epoxy resin at 127°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:31), and stir until the solution is light yellow and transparent; put it into a vacuum oven at 77°C for degassing for 28 minutes; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 126°C for 1.8 hours, then increase the temperature to 206°C and heat it for 1.8 hours to cure the resin; Step (6) Preparation of polyacrylate composite emulsion Deionized water was added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and the water bath was preheated to 62°C; according to the test formula, the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder were added to the four-necked flask and heated in a water bath at 76°C. After the powder and the core pre-emulsion liquid were mixed evenly by high-speed stirring, the initiator (NH4)2S2O8 (2.5mL / h) and the buffer Na2HPO4 (2.5mL / h) were added, and the core layer emulsion was formed after high-speed mechanical stirring for 1.8h; After the core layer emulsion is formed, an emulsifier (nonylphenol polyoxyethylene ether ammonium sulfate, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture; water-oil ratio is 1:60) is added and the shell pre-emulsion is uniformly added dropwise through a constant pressure funnel (2.2h / 5min); after two hours, the shell pre-emulsion is added dropwise, the water bath temperature is raised to 80°C, the initiator (NH4)2S2O8 (2.6mL / h) and the buffer Na2HPO4 (2.6mL / h) are added and kept warm for 0.7 hours; after the reaction is completed, the material is discharged at 73°C, cooled to room temperature and then the polyacrylate composite emulsion is allowed to stand; Step (7) Metallized polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (5) on a clean glass plate, dip the polyacrylate composite emulsion prepared in step (6) with a paint brush, evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 90°C for 9.6 minutes, take out the glass plate, and peel off the aramid fiber bundle composite material from the glass plate.

[0033] Comparative Example 1

[0034] Step (1) Aramid fiber surface cleaning Take a 3.1m long fiber bundle and place it in a 300mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it twice at 33kHz, each time for 24 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber prepared in step (1) is placed in a 32 g / L potassium hydroxide solution at 42°C and continuously stirred with ultrasonic vibration to remove oil stains on the fiber surface and roughen it, and then cleaned with distilled water; neutralization: the aramid fiber degreased and roughened through the degreasing, roughening, sensitization, activation and reduction steps is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: The neutralized aramid fiber was placed in a sensitizing solution (11 g·L -1of stannous chloride and 31ml·L -1 Hydrochloric acid (d = 118 g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: Place the degreased and roughened fibers in an activation solution (0.43 g·L -1 of palladium chloride and 9.0ml·L -1 Hydrochloric acid (d = 118 g cm -3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: The sensitized and activated fibers were placed in 25 g·L -1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface; Step (3) Chemical metallization of aramid fiber surface Weigh 15g of main salt (copper sulfate), 50g of complexing agent (sodium citrate), 76g of reducing agent (sodium hypophosphite), 0.44mg of stabilizer (sodium thiosulfate), and 0.045mg of compounding agent (sodium potassium tartrate) and dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (2) to the main salt solution dissolved in advance; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution and filter the plating solution; Step (4) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin at 124°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:34), stir until the solution is light yellow and transparent; put it into a vacuum oven at 78°C for degassing for 24 minutes; put the chemically metallized aramid fiber prepared in step (3) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 124°C for 1.6 hours, then increase the temperature to 207°C and heat it for 1.6 hours to cure the resin; Step (5) Preparation of polyacrylate composite emulsion Deionized water was added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and the water bath was preheated to 62°C; according to the test formula, the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder were added to the four-necked flask and heated in a water bath at 77°C. After the powder and the core pre-emulsion liquid were mixed evenly by high-speed stirring, the initiator (NH4)2S2O8 (2.6mL / h) and the buffer Na2HPO4 (2.6mL / h) were added, and the core layer emulsion was formed after high-speed mechanical stirring for 1.8h; After the core layer emulsion is formed, an emulsifier (ammonium sulfate of nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture; water-to-oil ratio is 1:62) is added and the shell pre-emulsion is uniformly added dropwise through a constant pressure funnel (2.3h / 5min); after two hours, the addition of the shell pre-emulsion is completed, the water bath temperature is raised to 80°C, an initiator (NH4)2S2O8 (2.6mL / h) and a buffer Na2HPO4 (2.6mL / h) are added and kept warm for 0.7 hours; after the reaction is completed, the material is discharged at 74°C, cooled to room temperature and allowed to stand, and the polyacrylate composite emulsion is applied to the aramid fiber tow composite material prepared in step (4); Step (6) Metallized polymer flame retardant fiber material Cut the aramid fiber bundle composite material prepared in step (4) and lay it flat on a clean glass plate. Use a paint brush to dip the polyacrylate composite emulsion prepared in step (5) and evenly apply it on the surface. Then place the two together in a vacuum drying oven and dry them at 93°C for 9.4 minutes. Take out the glass plate and peel off the aramid fiber bundle composite material from the glass plate.

[0035] Comparative Example 2

[0036] Step (1) Aramid fiber pretreatment The aramid fiber is placed in a 31g / L potassium hydroxide solution at 40°C and continuously stirred with ultrasonic vibration to remove oil stains on the fiber surface and roughen it, and then cleaned with distilled water; neutralization: the aramid fiber that has been degreased and roughened through the degreasing, roughening, sensitization, activation and reduction steps is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Activation: Place the degreased and roughened fibers in an activation solution (0.42 g·L -1 of palladium chloride and 9.2 ml·L -1 Hydrochloric acid (d = 118 g cm -3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: The activated fiber was placed in 26g·L-1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface; Step (2) Dopamine modified aramid fiber A 1 g / L dopamine solution is prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane is added to adjust the pH value to 8.4, and the solution is placed in a magnetic stirrer; the aramid fiber tow pretreated in step (1) is then wound on a rack and placed in the dopamine solution, the magnetic stirrer is turned on, and the mixture is stirred at 28° C.; the fiber is then washed with water and dried for later use; Step (3) Chemical metallization of aramid fiber surface Weigh 19g of main salt (copper sulfate), 66g of complexing agent (sodium citrate), 71g of reducing agent (sodium hypophosphite), 0.41mg of stabilizer (sodium thiosulfate), and 0.041mg of compounding agent (sodium potassium tartrate) and dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (2) to the pre-dissolved main salt solution; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution and filter the plating solution; Step (4) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin at 125°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:30), and stir until the solution is light yellow and transparent; put it into a vacuum oven at 75°C for degassing for 25 minutes; put the chemically metallized aramid fiber prepared in step (3) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 125°C for 2 hours, then increase the temperature to 200°C and heat it for 2 hours to cure the resin; Step (5) Preparation of polyacrylate composite emulsion Deionized water was added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and the water bath was preheated to 60°C; according to the test formula, the core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder were added to the four-necked flask and heated in a water bath at 76°C. After the powder and the core pre-emulsion liquid were mixed evenly by high-speed stirring, the initiator (NH4)2S2O8 (2.2mL / h) and the buffer Na2HPO4 (2.2mL / h) were added, and the core layer emulsion was formed after high-speed mechanical stirring for 2h; After the core layer emulsion is formed, an emulsifier (ammonium sulfate of nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture; water-to-oil ratio is 1:61) is added and the shell pre-emulsion is uniformly added dropwise (2h / 5min) through a constant pressure funnel; after two hours, the addition of the shell pre-emulsion is completed, the water bath temperature is raised to 75°C, an initiator (NH4)2S2O8 (2.2mL / h) and a buffer Na2HPO4 (2.2mL / h) are added and kept warm for 0.6 hours; after the reaction is completed, the material is discharged at 74°C, cooled to room temperature and allowed to stand, and the polyacrylate composite emulsion is applied to the aramid fiber tow composite material prepared in step (4); Step (6) Metallized polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (4) on a clean glass plate, dip the polyacrylate composite emulsion prepared in step (5) with a paint brush, evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 93°C for 9.4 minutes, take out the glass plate, and peel off the aramid fiber bundle composite material from the glass plate.

[0037] Comparison of detection experiments: The metallized polymer flame-retardant fiber materials obtained in Examples 1 to 4 and the comparative products 1 and 2 were tested. The specific testing method is as follows: Oxygen index detection method Place the material vertically in a mixed flow of oxygen and nitrogen, apply a flame at the upper end, and measure the minimum oxygen concentration (called oxygen index) required for the material to just maintain combustion. It is expressed as a volume percentage (%) to determine the flame retardancy of the material.

[0038] Tensile force testing method An electronic strength tester (Model YG020A) was used to apply tension to the fiber material, measure its breaking strength, and evaluate its flexibility. The speed of the machine was set to 250 mm / min. A total of 30 tests were performed on each material, and the average value of the results was taken.

[0039] Air permeability test Breathability is an important indicator of thermal and hygroscopic comfort of materials. This test is performed to evaluate the comfort of materials. The material is clamped in the tester and pressurized air is passed through the fabric using a vacuum. The breathability of the material is determined from the air flow rate. The test conditions are: No. 5 nozzle, sample area 20cm, and ten tests are performed for each sample and the average of the results is taken.

[0040] Direct test and comparison method of sensor data For the physiological index detection speed, the wearable health monitoring device made of the metallized polymer flame-retardant fiber material prepared in different embodiments is directly used for physical monitoring and statistical measurement; the sensor test is divided into two parts, namely the test of the heart rate sensor and the temperature sensor; to improve the accuracy of the test, all tests are measured simultaneously, and for the measurement of the human body surface temperature, a thermometer and a sensor are used for simultaneous measurement, and the main detection site is the left rib; for the measurement of heart rate, manual observation is adopted, that is, the pulse is calculated by taking the pulse within a fixed time, and the manual and equipment measurement values ​​are obtained. A total of twenty tests are carried out for each material, and then the average relative error rate (%) is calculated by the average relative error formula and the average value of the results is taken.

[0041] Table 1 Flame retardancy test results

[0042] As can be seen from Table 1, Example 4 is the best, while Comparative Example 2 is the worst. Since the fiber material is pretreated to different degrees and the polyacrylate composite emulsion is applied, that is, the nano flame retardant powder is evenly dispersed in the polyacrylate emulsion by stirring and dispersing for different lengths of time, agglomeration is avoided, and the stability and dispersion uniformity of the powder in the emulsion are improved; thus, the flame retardancy of the monitoring equipment is good; on the contrary, the composite emulsion with a relatively uneven dispersion degree of the nano flame retardant powder leads to poor flame retardancy of the material.

[0043] Table 2 Tensile test results

[0044] Table 3 Air permeability test results

[0045] It can be seen from Tables 2 and 3 that the air permeability of the material is improved with the addition of tris(hydroxymethyl)aminomethane to the dopamine solution for different treatment times and the long-term degassing of the fiber material in the E-51 epoxy resin, which is conducive to improving the adhesion of dopamine, allowing it to be deposited on the surface of the aramid fiber, increasing the surface activity of the fiber, and improving the aramid fiber tow composite material; the flexibility and tension of the material are increased, which in turn affects the weavability of the fiber material, and the air permeability and comfort of the device are also increased, which is conducive to monitoring physiological indicators and makes the device have good biocompatibility.

[0046] Table 4 Error test results of monitoring physiological indicators

[0047] It can be seen from the results in Table 4 that the data accuracy of Example 4 is the best. The conductivity and flame retardancy of the metal polymer flame retardant fiber materials prepared under different conditions are different, which also have different effects on the monitoring data error rate of the device sensor element; during the continuous monitoring process of the device, the accuracy of the physiological data also varies; its accuracy helps to capture subtle changes in physiological indicators and provide richer data support for clinical decision-making.

[0048] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A process for preparing a metallized polymer flame-retardant fiber material, comprising: step (1) cleaning the surface of aramid fiber, step (2) pretreating the aramid fiber, step (3) modifying the aramid fiber with dopamine, step (4) chemically metallizing the surface of the aramid fiber, step (5) preparing an aramid fiber tow composite material, step (6) preparing a polyacrylate composite emulsion, and step (7) preparing the metallized polymer flame-retardant fiber material; in, Step (2) Aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a potassium hydroxide solution, and continuously stirred with ultrasonic vibration, and roughened, and then cleaned with distilled water; the degreased and roughened aramid fiber is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in the sensitizing solution and stir it continuously to make a layer of easily oxidized substances adsorbed on the fiber surface. During the activation treatment, the activation solution is reduced to form catalytic crystal nuclei, which are adsorbed on the surface of the fiber and then rinsed with distilled water; Activation: Place the sensitized fiber in the activation solution and stir it vigorously to form a layer of palladium metal particles with catalytic activity on the fiber surface, and then rinse it with distilled water; Reduction: The activated fiber is placed in a sodium hypophosphite solution for reduction treatment to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber Dopamine hydrochloride and distilled water are used to prepare a dopamine solution, and tris(hydroxymethyl)aminomethane is added to adjust the pH value; Then, the aramid fiber tow pretreated in step (2) is wound on a rack and placed in a dopamine solution for stirring, and then the fiber is washed with water and dried for later use.

2. The process for preparing the metallized polymer flame retardant fiber material according to claim 1, characterized in that: Step (1) Aramid fiber surface cleaning Place the fiber bundle in a conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner for cleaning, wash the fiber after ultrasonic cleaning with acetone with clean water, put it in an oven for drying, and then put it in a sealed bag for storage; Step (2) Aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a potassium hydroxide solution, and continuously stirred with ultrasonic vibration, and roughened, and then cleaned with distilled water; the degreased and roughened aramid fiber is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in a sensitizing solution (a mixture of stannous chloride and hydrochloric acid) and stir continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface. During the activation treatment, the activation solution is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface and then rinsed with distilled water. Activation: Place the sensitized fiber in an activation solution (a mixture of palladium chloride and hydrochloric acid) and stir vigorously to form a layer of palladium metal particles with catalytic activity on the fiber surface, and then rinse it with distilled water; Reduction: The activated fiber is placed in a sodium hypophosphite solution for reduction treatment to remove the activation solution remaining on the fiber surface; Step (3) Dopamine modified aramid fiber A dopamine solution was prepared using dopamine hydrochloride and distilled water, tris(hydroxymethyl)aminomethane was added to adjust the pH value, and the solution was placed in a magnetic stirrer; Then, the aramid fiber tow pretreated in step (2) is wound on a rack and placed in a dopamine solution, a magnetic stirrer is turned on for stirring, and then the fiber is washed with water and dried for later use; Step (4) Chemical metallization of aramid fiber surface Add the main salt (copper sulfate), complexing agent (sodium citrate), reducing agent (sodium hypophosphite), stabilizer (sodium thiosulfate), and compounding agent (sodium potassium tartrate), and then use distilled water to dissolve the main salt solution; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the pre-dissolved main salt solution, and add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution, and filter the plating solution; Step (5) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin, add curing agent (a mixture of epoxy resin and DDS (diaminodiphenyl sulfone)) into it, and stir until the solution is light yellow and transparent; put it into a vacuum oven for degassing; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold, put it into the oven for heating, and then continue to heat it after the temperature rises to cure the resin; Step (6) Preparation of polyacrylate composite emulsion Deionized water is added to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and preheated in a water bath; a core pre-emulsion liquid (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and a solution of dispersed nano flame retardant powder are added to the four-necked flask, and heated in a water bath at the same time. After the powder and the core pre-emulsion liquid are uniformly mixed by high-speed stirring, an initiator (NH4)2S2O8 and a buffer Na2HPO4 are added, and a core layer emulsion is formed after high-speed mechanical stirring; After the core layer emulsion is formed, an emulsifier (nonylphenol polyoxyethylene ether ammonium sulfate, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and water mixture) is added and the shell pre-emulsion is added dropwise at a uniform speed through a constant pressure funnel; after the shell pre-emulsion is added dropwise, an initiator (NH4)2S2O8 and a buffer Na2HPO4 are added and then kept warm; after the reaction is completed, the material is discharged, cooled to room temperature and then the polyacrylate composite emulsion is allowed to stand; Step (7) Metallized polymer flame retardant fiber material The aramid fiber bundle composite material prepared in step (5) is spread flat on a clean glass plate, and the polyacrylate composite emulsion prepared in step (6) is dipped into a paint brush and evenly coated on the surface. The two are placed together in a vacuum drying oven to dry, and the glass plate is taken out and the aramid fiber bundle composite material is peeled off from the glass plate.

3. The use of the preparation process of the metallized polymer flame retardant fiber material according to claim 2 is characterized by: Step (1) Aramid fiber surface cleaning Take a 3-4 m long fiber bundle and place it in a 300-400 mL conical flask, pour acetone until it covers the fiber bundle, place the conical flask in an ultrasonic cleaner, and clean it 3-4 times at 30-40 kHz, each time for 20-30 minutes; wash the fiber after acetone ultrasonic cleaning with clean water, put it in an oven to dry, and then put it in a sealed bag for later use.

4. The process for preparing the metallized polymer flame retardant fiber material according to claim 3, characterized in that: Step (2) Aramid fiber pretreatment The aramid fiber after cleaning in step (1) is placed in a 30-35 g / L potassium hydroxide solution at 40-45° C., and continuously stirred with ultrasonic vibration, and roughened, and then cleaned with distilled water, and the roughened aramid fiber is placed in a dilute acid, and the alkali remaining on the fiber surface is cleaned with distilled water; Sensitization: Place the neutralized aramid fiber in a sensitizing solution (10~15g·L -1 of stannous chloride and 30~35ml·L -1 Hydrochloric acid (d = 118 ~ 119g cm -3) The fiber surface is placed in a mixture of 20% tantalum and 1% tantalum (aqueous mixture of 20% tantalum and 1% tantalum) and stirred continuously to allow a layer of easily oxidizable substances (tin chloride) to be adsorbed on the fiber surface, so that during the activation treatment, the activation liquid is reduced to form catalytic crystal nuclei, which are adsorbed on the fiber surface, and then rinsed with distilled water to prevent the catalytic crystal nuclei from being washed away; Activation: Place the sensitized fiber in an activation solution (0.4~0.5g·L -1 of palladium chloride and 9~10ml·L -1 Hydrochloric acid (d = 118 ~ 119 g cm -3 ) in a mixed solution) with strong stirring to form a layer of palladium metal particles with catalytic activity on the fiber surface, which is then rinsed with distilled water; Reduction: Place the activated fiber in a 25~30g·L -1 Reduction treatment is carried out in a sodium hypophosphite solution to remove the activation solution remaining on the fiber surface.

5. The process for preparing the metallized polymer flame retardant fiber material according to claim 4, characterized in that: Step (3) Dopamine modified aramid fiber Use dopamine hydrochloride and distilled water to prepare a 1-2 g / L dopamine solution, add tris(hydroxymethyl)aminomethane to adjust the pH value to 8.4-8.5, and place the solution in a magnetic stirrer; Then, the aramid fiber tow pretreated in step (2) is wound on a rack and placed in a dopamine solution, and a magnetic stirrer is turned on to stir at 25-30° C. for 1-13.5 h. The fibers are then washed with water and dried for later use.

6. The process for preparing the metallized polymer flame retardant fiber material according to claim 5, characterized in that: Step (4) Chemical metallization of aramid fiber surface Weigh 15-25 g of main salt (copper sulfate), 50-80 g of complexing agent (sodium citrate), 70-90 g of reducing agent (sodium hypophosphite), 0.40-0.50 mg of stabilizer (sodium thiosulfate), and 0.04-0.05 mg of compounding agent (sodium potassium tartrate); dissolve the main salt solution with distilled water; add the complexing agent and the aramid fiber modified with dopamine in step (3) to the pre-dissolved main salt solution; add the reducing agent to the prepared plating solution; stir the stabilizer and compounding agent evenly and pour them into the prepared plating solution; dilute with distilled water and oscillate with ultrasound; adjust the plating solution value with acid or alkali solution and filter the plating solution.

7. The process for preparing the metallized polymer flame retardant fiber material according to claim 6, characterized in that: Step (5) Preparation of aramid fiber tow composite material Heat and stir E-51 epoxy resin at 125-130°C, add DDS curing agent (mass ratio of epoxy resin to DDS (diaminodiphenyl sulfone) is 100:30-100:35), and stir until the solution is light yellow and transparent; put it into a vacuum oven at 75-80°C for degassing for 25-30 minutes; put the chemically metallized aramid fiber prepared in step (4) into the slit of the mold and clamp it, then pour the degassed resin into the mold and put it into the oven, heat it at 120-130°C for 1.5-2 hours, then raise the temperature to 200-210°C and heat it for 1.5-2 hours to cure the resin.

8. The process for preparing the metallized polymer flame retardant fiber material according to claim 7, characterized in that: Step (6) Preparation of polyacrylate composite emulsion Add deionized water to a four-necked flask equipped with a stirrer, a thermometer, a condenser and a constant pressure funnel, and preheat it in a water bath to 60-65°C; according to the test formula, add the core pre-emulsion (a mixture of emulsifier OP-10 (alkylphenol polyoxyethylene ether) and sodium dodecyl sulfate (SDS)) and the solution of dispersed nano flame retardant powder into the four-necked flask and heat it in a water bath at 77-78°C. After the powder and the core pre-emulsion are evenly mixed by high-speed stirring, add the initiator (NH4)2S2O8 (2-3mL / h) and the buffer Na2HPO4 (2-3mL / h), and form a core layer emulsion after high-speed mechanical stirring for 1.5-2h; After the core layer emulsion is formed, an emulsifier (ammonium sulfate of nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether, a mixture of sodium dodecyl sulfate and water; the water-oil ratio is 1:60~1:65) is added and the shell pre-emulsion is uniformly added through a constant pressure funnel (2~2.5h / 5min); after 1-2 hours, the shell pre-emulsion is added, the temperature of the water bath is raised to 75~80℃, and the initiator (NH4)2S2O8 (2~3mL / h) and the buffer (2~3mL / h) are added and kept warm for 0.5~1 hour; after the reaction is completed, the material is discharged at 74~76℃, cooled to room temperature and then the polyacrylate composite emulsion is allowed to stand.

9. The process for preparing the metallized polymer flame retardant fiber material according to claim 8, characterized in that: Step (7) Metallized polymer flame retardant fiber material Spread the aramid fiber bundle composite material prepared in step (5) on a clean glass plate, dip a paint brush into the polyacrylate composite emulsion prepared in step (6), evenly apply it on the surface, and then place the two together in a vacuum drying oven, dry at 90-95°C for 9-10 minutes, take out the glass plate, and peel off the aramid fiber bundle composite fiber mesh cloth from the glass plate.

10. Application of metallized polymer flame retardant fiber material in wearable health monitoring equipment, characterized in that Wearable health monitoring equipment can be made using the metallized polymer flame retardant fiber material prepared according to the preparation process of the metallized polymer flame retardant fiber material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing conductive ultrahigh molecular weight polyethylene fiber

    CN102277728A

  • Method for preparing surface silver-plated electric-spinning fiber by using dopamine

    CN103276379A

  • Method for preparing dacron electric conduction fiber with metallic compound as electric conduction component

    CN105484043A

  • Method for preparing surface metallization aramid fibers

    CN109554916A

  • Surface metallized fiber and preparation method thereof

    CN117947634A